Sustainable Infrastructure Development in The IKN Region (Nusantara Capital): Simulation of The Smart Self-Sustaining Urban Center Area Development - Laksono, Naufal Budi; Latief, Yusuf (Smart City, 2024)
Embarking on the quest for a sustainable urban future, this research immerses itself in the vibrant landscape of "Sustainable Infrastructure Development in the IKN Region (Nusantara Capital)." This study investigates the financial viability and economic attractiveness of the Five City project, focusing on efficient infrastructure management for sustainable settlement development. The core facility comprises four vertical residential towers with supporting amenities. The research aims to evaluate the project''s feasibility over a 25-year investment period through comprehensive financial analyses.The research employs a structured approach, encompassing regulatory analysis, stakeholder identification, financial capability analysis, and risk management. Parameters such as Net Present Value (NPV), Benefit/Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period are used for economic feasibility analysis. The study employs a detailed Risk Breakdown Structure (RBS) and Risk Register for risk management. The results collectively highlight the project''s promising economic outlook and proactive risk management approach.In conclusion, the study underscores the feasibility of the Five City project as a sound venture in project financing. The findings contribute valuable insights into infrastructure development, project finance, and risk management, providing a blueprint for sustainable housing projects in the Nusantara Capital Region. Recommendations include continuous monitoring, transparent communication, and adaptability for long-term success.